beta-decay matrix elements from the study of asymmetric emission from polarised nuclei: gamma-tagging - a new method for complex beta-decay - Giles, T; Williams, D; Stone, N; Rikovska, J (1999)
A new method is introduced designed to facilitate study of matrix elements in complex beta-decay through the measurement of asymmetric beta-emission from a low-temperature polarised source. The method involves coincident detection of the beta-emission with subsequent gamma-transitions to tag the beta-spectrum component. The method is demonstrated by application to the decay of La-140.